Weevil endosymbiont dynamics is associated with a clamping of immunity. (December 2015) - Masson, Florent; Moné, Yves; Vigneron, Aurélien; Vallier, Agnès; Parisot, Nicolas; Vincent-Monégat, Carole; Balmand, Séverine; Carpentier, Marie-Christine; Zaidman-Rémy, Anna; Heddi, Abdelaziz
Abstract Background Insects subsisting on nutritionally unbalanced diets have evolved long-term mutualistic relationships with intracellular symbiotic bacteria (endosymbionts). The endosymbiont population load undergoes changes along with insect development. In the cereal weevilSitophilus oryzae, the midgut endosymbiontsSodalis pierantonius drastically multiply following adult metamorphosis and rapidly decline until total elimination when the insect achieves its cuticle synthesis. Whilst symbiont load was shown to timely meet insect metabolic needs, little is known about the host molecular and immune processes underlying this dynamics. Methods We performed RNA sequencing analysis on weevil midguts at three representative phases of the endosymbiont dynamics (i.e. increase, climax and decrease). To screen genes which transcriptional changes are specifically related to symbiont dynamics and not to the intrinsic development of the midgut, we further have monitored by RT-qPCR sixteen gene transcript levels in symbiotic and artificially non-symbiotic (aposymbiotic) weevils. We also localized the endosymbionts during the elimination process by fluorescence microscopy. Results Functional analysis of the host differentially expressed genes by RNA sequencing showed that the main transcriptional changes occur during endosymbiont growth phase and affect cell proliferation, apoptosis, autophagy, phagocytosis, and metabolism of fatty acids and nucleic acids. We also showed that symbiont dynamics alters the expression of several genes involved in insect development. Our results strengthened the implication of apoptosis and autophagy processes in symbiont elimination and recycling. Remarkably, apart from the coleoptericin A that is known to target endosymbionts and controls their division and location, no gene coding antimicrobial peptide was upregulated during the symbiont growth and elimination phases. Conclusion We show that endosymbiont dynamics parallels numerous transcriptional changes in weevil developing adults and affects several biological processes, including metabolism and development. It also triggers cell apoptosis, autophagy and gut epithelial cell swelling and delamination. Strikingly, immunity is repressed during the whole process, presumably avoiding tissue inflammation and allowing insects to optimize nutrient recovery from recycled endosymbiont.